2013
DOI: 10.1017/s0033291713001839
|View full text |Cite
|
Sign up to set email alerts
|

Altered social and non-social decision-making in recreational and dependent cocaine users

Abstract: Background Maladaptive decision-making is assumed to be a core feature of cocaine addiction. Indeed, numerous studies have reported deficits in non-social decision-making tasks and reward-related impulsivity in dependent cocaine users. However, social decision-making has not been examined in cocaine users yet. Moreover, it is unknown if even recreational and non-dependent cocaine use is linked to decisionmaking deficits. Therefore, we investigated whether recreational and dependent cocaine users exhibit altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
102
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 69 publications
(97 reference statements)
7
102
0
3
Order By: Relevance
“…The present data were collected in the context of the Zurich Cocaine Cognition Study (13,15,55,56). For study I, 80 CUs and 63 stimulant drug-naïve control participants were included, whereas a subpopulation of 16 CUs and 16 HCs participated in study II (for recruitment details, see SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data were collected in the context of the Zurich Cocaine Cognition Study (13,15,55,56). For study I, 80 CUs and 63 stimulant drug-naïve control participants were included, whereas a subpopulation of 16 CUs and 16 HCs participated in study II (for recruitment details, see SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Previous results suggest that cocaine users (CUs) show impairments in different facets of social cognition, particularly in emotional empathy, mental perspective taking, and emotion recognition in prosody, which are related to deficits in real-life social behavior such as fewer social contacts and more criminal offenses (13,14). Furthermore, in money distribution games, CUs act more self-servingly and less altruistically than stimulant-naïve controls (15). Volkow et al (9) postulated that neuroadaptations in the reward systems of drug users (e.g., ventral striatum and orbitofrontal cortex) alter reward processing such that the value of the abused drug is enhanced and concurrently the value of nondrug rewards, including social interaction, is reduced.…”
mentioning
confidence: 99%
“…Prior studies have consistently shown that dependent cocaine users exhibit disadvantageous decision-making strategies in tasks such as the Iowa Gambling Task (IGT) and preferences for smaller immediate over larger but delayed rewards as measured with the Delay Discounting Task (DD) (Bechara et al 2002;Hulka et al 2014;Kjome et al 2010;Verdejo-Garcia et al 2007). Impulsivity, a multi-facetted concept, is generally defined as a predisposed tendency toward rapid and unplanned reaction patterns without much foresight regarding possible consequences (Moeller et al 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…A paramount question is whether social reward deficits are a cause or a consequence of cocaine addiction. This very same laboratory has provided preliminary evidence regarding this question, showing that social decision-making deficits occur in both recreational and dependent cocaine users (19), therefore suggesting social deficits are a vulnerability factor for cocaine addiction. However, it is also well known that cocaine detrimentally impacts orbitofrontal cortex functions (20), such that even recreational exposure to cocaine may impair or worsen the orbitofrontal ability to properly weigh up social bonds and social rules.…”
mentioning
confidence: 99%